Global feasibility assessment of interrupting the transmission of soil-transmitted helminths: a statistical modelling study. Issue 8 (August 2015) - Brooker, Simon J; Nikolay, Birgit; Balabanova, Dina; Pullan, Rachel L
Summary Background Emphasis is being given to the control of neglected tropical diseases, including the possibility of interrupting the transmission of soil-transmitted helminths (STH). We evaluated the feasibility by country of achieving interruption of the transmission of STH. Methods Based on a conceptual framework for the identification of the characteristics of a successful STH control programme, we assembled spatial data for a range of epidemiological, institutional, economic, and political factors. Using four different statistical methods, we developed a composite score of the feasibility of interrupting STH transmission and undertook a sensitivity analysis of the data and methods. Findings The most important determining factors in the analysis were underlying intensity of STH transmission, current implementation of control programmes for neglected tropical diseases, and whether countries receive large-scale external funding and have strong health systems. The composite scores suggested that interrupting STH transmission is most feasible in countries in the Americas and parts of Asia (eg, Argentina [range of composite feasibility scores, depending on scoring method, 9·4–10·0], Brazil [8·7– 9·7], Chile [8·84–10·0], and Thailand [9·1–10·0]; there was perfect agreement between the four methods), and least feasible in countries in sub-Saharan Africa (eg, Congo [0·4–2·7] and Guinea [2·0–5·6]; there was full agreement between methods), but there were important exceptions to these trends (eg, Ghana [7·4–10·0]; there was agreement between three methods). Agreement was highest between the scores derived with the expert opinion and principal component analysis weighting schemes (Pearson correlation coefficient, r=0·98). The largest disagreement was between benefit-of-the-doubt-derived and principal-component-analysis-derived weighting schemes (r=0·74). Interpretation The interruption of STH transmission is feasible, especially in countries with low intensity of transmission, supportive household environments, strong health systems, and the availability of suitable delivery platforms and in-country funds, but to achieve local elimination of STH an intersectoral approach to STH control will be needed. Funding Bill & Melinda Gates Foundation and Wellcome Trust.